Perspectives: Resilient forests need joint forces for better inventorying and monitoring - Ferretti, Marco; Gessler, Arthur; Cools, Nathalie; Fleck, Stefan; Guerrieri, Rossella; Jakovljević, Tamara; Nicolas, Manuel; Nieminen, Tiina M.; Pitar, Diana; Potočić, Nenad; Raspe, Stephan; Schaub, Marcus; et al. (Elsevier, 2024)
Forests are increasingly affected by global change. Building resilient forests requires – amongst others - leveraging the wealth of knowledge from existing ground-based, field inventory and monitoring programs as well as Earth Observation systems to better assess the status, detect changes, understand processes, predict future dynamics, and guide forest management. A proposal from the European Commission for a new forest monitoring framework at the European level aims in this direction but lacks the integration of some crucial and readily available resources and infrastructures. For this reason, the proposal risks to be a missed opportunity rather than a step forward. Here we provide suggestions to help reconciling the proposal with its objectives and a more comprehensive monitoring vision.
Keywords: forest; monitoring; European Union countries; perspective; network environment